Evaluación de control interno al departamento de créditos y cobranzas de la cooperativa de ahorro y crédito monseñor Leónidas Proaño, ubicada en el cantón Latacunga provincia de Cotopaxi en el periódo económico 2017. - Cofre Herrera, Elvia Beatriz (2018)
The present research project was carried out at the Monseñor Leónidas Proaño Savings and Credit Union, located in the province of Cotopaxi, Latacunga city, proposing as a general objective to Evaluate the Internal Control to the Credit and Collections Department in the 2017 economic period, to carry out good credit management and manage the potential and real risks that affect economic resources. The methodology used for the realization of the research project is based on the deductive method that starts from general and valid data, deducting the logical reasoning with studies of frequent principles to verify its validity. The inductive method that serves to obtain a global knowledge of internal control. The techniques used are the surveys and the interview that was carried out with the clients, manager and head of credits, which was necessary to assess the study entity, internal control questionnaire that evaluated the cooperative's processes, establishing weak points and posing tools of control and corrective operations. As results obtained through the evaluation of internal control will reduce the risk and increase the level of security in terms of obtaining the objectives in relation to the efficiency and validity of the processes in turn the reliability of administrative information to compliance of methods, tools and strategies applied.